Synthesis and characterization of antibacterial drug loaded beta-tricalcium phosphate powders for bone engineering applications - OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (SPRINGER, 2020)
Powders of beta-tricalcium phosphate [beta-TCP, beta-Ca-3(PO4)(2)] and composite powders of beta-TCP and polyvinyl alcohol (PVA) were synthesized by using wet precipitation methods. First, the conditions for the preparation of single phase beta-TCP have been delineated. In the co-precipitation procedure, calcium nitrate and diammonium hydrogen phosphate were used as calcium and phosphorous precursors, respectively. The pH of the system was varied in the range 7-11 by adding designed amounts of ammonia solution. The filtered cakes were desiccated at 80 degrees C and subsequently calcined at different temperatures in the range between 700-1100 degrees C. Later on, rifampicin form II was used to produce drug-loaded beta-TCP and PVA/beta-TCP powders. All the synthesized materials have been characterized from morphological (by scanning electron microscopy) and structural-chemical (by X-ray diffraction and Fourier transform infrared spectroscopy) point of view. The drug loading capacity of the selected pure beta-TCP powder has been assessed. The biological performance (cytocompatibility in fibroblast cell culture and antibacterial efficacy against Escherichia coli and Staphylococcus aureus) has been tested with promising results. Application perspectives of the designed drug-bioceramic-polymer blends are advanced and discussed. [GRAPHICS] .
Keywords: IN-VITRO; CALCIUM PYROPHOSPHATE; ANTIMICROBIAL ACTIVITY; BIOLOGICAL-PROPERTIES; MECHANICAL-PROPERTIES; JOINT INFECTIONS; SOLID-STATE; RIFAMPICIN; HYDROXYAPATITE; NANOPARTICLES